Characteristics of students in developing reflective thinking in basic algebra - Nursupiamin, Nursupiamin; Ramlah, Ufiyah; Putri, Hestina (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: Low reflective thinking skills are often linked to learning approaches that do not foster critical and reflective abilities. This study aims to examine the contribution of student characteristics, based on the Big Five personality traits, to the development of reflective thinking skills in basic algebra.Method: A mixed-methods approach with a sequential explanatory design was employed, integrating quantitative and qualitative data. The quantitative phase involved administering questionnaires and tests to 229 students in Palu, Indonesia was selected through stratified random sampling. The research variables included student characteristics (measured using the Big Five scale) and reflective thinking skills in basic algebra. Data were analyzed using SPSS, including validity and reliability tests, descriptive statistics, classical assumption tests, and linear regression. The qualitative phase involved interviews, with data validity ensured through triangulation and member checking.Findings: The results indicate that student personality characteristics contribute 17.9 percent to reflective thinking skills in basic algebra. Specifically, extroversion contributed 3.4 percent, agreeableness 7.5 percent, conscientiousness 9.2 percent, neuroticism 12.9 percent, and openness to experience 4.8 percent. Among these, conscientiousness and neuroticism were the dominant influencing factors. However, further analysis revealed that openness to experience and conscientiousness significantly enhance reflective thinking, while neuroticism does not have a significant impact. Openness to experience supports creativity and critical thinking, whereas conscientiousness is linked to discipline and structured learning, both of which encourage reflection.Significance: These findings highlight the importance of considering individual personality traits when designing learning strategies to foster reflective thinking skills. By integrating personality-based approaches, educators can create more effective learning environments that enhance students’ ability to think reflectively in mathematics.